Near-Complete Genome Sequences of Measles Virus Strains from 10 Years of Uganda Country-wide Surveillance - Namuwulya, Prossy; Bukenya, Henry; Tushabe, Phionah; Tweyongyere, Robert; Bwogi, Josephine; Cotten, Matthew; Phan, My V. T. (Microbiology Resource Announcements, 2022)
Measles remains a global health challenge despite the availability of a safe and effective vaccine. Sporadic outbreaks of measles virus infections continue in Uganda. We report eight near-complete genome sequences of measles virus strains from Uganda cases from 2011 to 2020, providing useful data for assessing vaccine escape and local/regional transmission.